2018
DOI: 10.1111/ejh.13144
|View full text |Cite
|
Sign up to set email alerts
|

Immune thrombocytopenia: Effectiveness of frontline steroids and comparison of azathioprine, splenectomy, and rituximab as second‐line treatment

Abstract: Steroids are effective frontline treatment for ITP, but relapse is common. Both azathioprine and splenectomy are effective treatment after steroid failure. Rituximab appears to a reasonable second-line treatment option in our limited experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…Japanese health insurance). Azathioprine is reported to have a 40-60% efficacy rate with oral administration of 1-2 mg/kg/day (maximum dose 150 mg/day) [134,135]. Adverse drug reactions include myelosuppression, liver dysfunction, and pancreatitis.…”
Section: Azathioprine (Recommendation Level: 2c Not Covered Bymentioning
confidence: 99%
“…Japanese health insurance). Azathioprine is reported to have a 40-60% efficacy rate with oral administration of 1-2 mg/kg/day (maximum dose 150 mg/day) [134,135]. Adverse drug reactions include myelosuppression, liver dysfunction, and pancreatitis.…”
Section: Azathioprine (Recommendation Level: 2c Not Covered Bymentioning
confidence: 99%
“…Azathioprine dosed at 150mg/day has been reported to be effective in chronic refractory ITP [24,25]. One retrospective study spanning a six-month period demonstrated a response rate of 71.4%, with complete response in 38% of patients [24]. A prospective study of 53 patients showed a 64% response, with 40% maintaining a response after one year [25].…”
Section: Reviewmentioning
confidence: 99%
“…Another retrospective study of 96 patients found that 54% of patients responded to azathioprine, though only 2% had a sustained response [11]. Leukopenia and increases in transaminases were reported, as well as alopecia, gastrointestinal effects, and increased risk of malignancy, specifically lymphoma [24,25]. However, the sample sizes for many of these studies were small, so further studies are needed to solidify the evidence for the efficacy and safety of azathioprine.…”
Section: Reviewmentioning
confidence: 99%
“…4,5 The authors obtain a surprisingly high rate of success and explain the discrepancy with former studies with "difference in case enrollment and definition of response". 1 The outcome of a high number of ITP cases has improved since the addition of rituximab and thrombopoietin receptor agonists to the therapeutic arsenal. Nevertheless, there will always be patients not responding to these treatments or presenting contraindications, so that alternatives remain necessary.…”
Section: Dear Editormentioning
confidence: 99%
“…Nevertheless, there will always be patients not responding to these treatments or presenting contraindications, so that alternatives remain necessary. One of such valuable alternatives is danazol, which Chang et al 1 Overall, danazol appears as a good choice for the second-line treatment of ITP (especially in older patients) and is clearly at least as efficient as most of the other possibilities. A dosing of 200-400 mg daily is generally well tolerated.…”
Section: Dear Editormentioning
confidence: 99%